1991
DOI: 10.1111/j.1525-1314.1991.tb00559.x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated TEM, XRD and electron microprobe investigation of mixed‐layer chlorite–smectite from the Point Sal ophiolite, California

Abstract: Five basalt samples from the Point Sal ophiolite, California, were examined using HRTEM and AEM in order to compare observations with interpretations of XRD patterns and microprobe analyses. XRD data from ethylene-glycol-saturated samples indicate the following percentages of chlorite in mixed-layer chlorite-smectite identified for each specimen: (i) L2036 = 50%, (ii) L2035 = 70 and 20%, (iii) 1A-13 = 70%, (iv) 1B-42 = 70%, and (v) 1B-55 = 100%. Detailed electron microprobe analyses show that 'chlorite' analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…Higher substitutions of octahedral Fe 2+ for Mg 2+ in the chlorites may compensate for the distortions introduced by the substitution of the larger A13+ cation for Si 4+ in the tetrahedral sheet (Shau et al, 1990). However, Hillier (1993), Bettison-Varga et al (1991), andMackinnon (1997) found no changes in the Fe/Mg ratio of coexisting chlorites and corrensites. Our results indicate a clear difference between chlorite and corrensite compositions, with well-defined ranges for each phase (Figures 4 and 5).…”
Section: Compositional Variations Of Chlorite and Corrensitementioning
confidence: 74%
See 1 more Smart Citation
“…Higher substitutions of octahedral Fe 2+ for Mg 2+ in the chlorites may compensate for the distortions introduced by the substitution of the larger A13+ cation for Si 4+ in the tetrahedral sheet (Shau et al, 1990). However, Hillier (1993), Bettison-Varga et al (1991), andMackinnon (1997) found no changes in the Fe/Mg ratio of coexisting chlorites and corrensites. Our results indicate a clear difference between chlorite and corrensite compositions, with well-defined ranges for each phase (Figures 4 and 5).…”
Section: Compositional Variations Of Chlorite and Corrensitementioning
confidence: 74%
“…However, corrensite and chlorite may also form by replacement of biotite Peacor, 1994a, 1994b;Li et al, 1998) and amphibole (Meunier et al, 1988), or by reaction between Mg-rich carbonate and dioctahedral clay minerals (Hutcheon et al, 1980;Hillier, 1993). In recent years it has been debated whether the transition from smectite to chlorite occurs as a continuous progressive transformation characterized by random and regular interlayering of different proportions of the end-member phases, as described by Bettison-Varga et al (1991), or if such transition is more accurately described as discontinuous steps between discrete sincerite, corrensite, and chlorite (Shau et al, 1990;Hillier, 1993Hillier, , 1995Schiffman and Staudigel, 1995;Roberson et al, 1999). Shau and Peacor (1992) suggested that the continuous transition occurs within incompletely recrystallized samples (i.e., those affected by relatively low fluid/rock interactions), whereas for higher fluid/ rock ratios the discontinuous transformation is favored, and only the discrete phases are present.…”
Section: Introductionmentioning
confidence: 99%
“…The smectite-like interlayer of corrensite is defined by Si-rich tetrahedral sheets that give rise to a small interlayer net negative charge, which requires that the octahedral sheet have minimum dimensions as consistent with low Fe occupancy to minimize misfit. The analyses of corrensite and chlorite by , Bettison-Varga et al (1991), and Inoue and Utada (1991), however, show decreased or nearly constant Fe/(Mg + Fe) ratios concomitant with an increase of A1/(Si + A1) ratios in conversions of smectite to corrensite. Bettison-Varga et al (1991) suggested that such an inverse chemical relation may be due to a lack of ample fluid, resulting in diverse local chemical environments and formation processes.…”
Section: Compositional Relation Between Coexisting Corrensite and Chlmentioning
confidence: 99%
“…The analyses of corrensite and chlorite by , Bettison-Varga et al (1991), and Inoue and Utada (1991), however, show decreased or nearly constant Fe/(Mg + Fe) ratios concomitant with an increase of A1/(Si + A1) ratios in conversions of smectite to corrensite. Bettison-Varga et al (1991) suggested that such an inverse chemical relation may be due to a lack of ample fluid, resulting in diverse local chemical environments and formation processes. The wide distribution of data points in Figure 17 may be a reflection of local environments, but the general crystal-chemical relations between corrensite and chlorite remain consistent for most analyses obtained for the diagenetic sample.…”
Section: Compositional Relation Between Coexisting Corrensite and Chlmentioning
confidence: 99%
See 1 more Smart Citation